2005
DOI: 10.1603/0022-0493-98.2.279
|View full text |Cite
|
Sign up to set email alerts
|

Association of Beet Leafhopper (Hemiptera: Cicadellidae) with a Clover Proliferation Group Phytoplasma in Columbia Basin of Washington and Oregon

Abstract: At least 16 taxa of cicadellids and delphacids were tested by polymerase chain reaction (PCR) for the presence of a phytoplasma in the clover proliferation group, designated 16SrVI. Nucleic acid extracts from individual insects or groups of 5-10 were tested using PCR primers designed from the DNA sequence of 16S-23S rRNA or ribosomal protein genes of the pathogen. The beet leafhopper, Circulifer tenellus (Baker), was most often associated with the phytoplasma, with approximately 16% of the insects testing posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 31 publications
0
21
1
Order By: Relevance
“…In Oregon and Washington Balclutha spp. were not found associated with the Columbia Basin purple top phytoplasma (Crosslin et al 2005). However, the population density of this species is lower in Washington and Oregon (Munyaneza et al 2008) than the densities observed in our study (Table 1,.…”
Section: Snowi Was Common All 3 Years At Delta Junction Andcontrasting
confidence: 68%
See 1 more Smart Citation
“…In Oregon and Washington Balclutha spp. were not found associated with the Columbia Basin purple top phytoplasma (Crosslin et al 2005). However, the population density of this species is lower in Washington and Oregon (Munyaneza et al 2008) than the densities observed in our study (Table 1,.…”
Section: Snowi Was Common All 3 Years At Delta Junction Andcontrasting
confidence: 68%
“…Diseases caused by phytoplasmas have become increasingly important in the Pacific Northwest, with recent outbreaks of potato purple top disease in Washington and Oregon causing severe yield losses and reduction in tuber quality in potato (Crosslin et al 2005;Munyaneza et al 2006Munyaneza et al , 2007Munyaneza et al , 2008. In the Columbia Basin, the potato purple top disease is associated with the Columbia Basin purple top phytoplasma vectored by the beet leafhopper, Circulifer tenellus Baker (Lee et al 2004a;Crosslin et al 2005Crosslin et al , 2006Munyaneza et al , 2007; while in Mexico, and other potato producing areas of the USA, purple top is associated with aster leafhoppers in the genus Macrosteles (Hagel and Landis 1967;Hagel et al 1973;Bantari et al 1993;Goodwin et al 1999;Leyva et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This is similar to hopperburn symptoms on soybean inflicted by potato leafhopper, E. fabae (Hutchins & Pedigo 1990). In general, leafhoppers can also indirectly damage plants by transmitting plant pathogens such as phytoplasma on potato (Crosslin et al 2005;Munyaneza et al 2006) and viruses on rice (Hibino & Cabunagan 1986;Siwi & Suzuki 1991).…”
Section: Introductionmentioning
confidence: 86%
“…It has been determined that the beet leafhoppertransmitted virescence agent (BLTVA) phytoplasma, also known as 'Columbia Basin potato purple top phytoplasma', is the causal agent of the disease in the Columbia Basin and that this pathogen is transmitted by the beet leafhopper, Circulifer tenellus (Lee et al 2004;Crosslin et al 2005;Munyaneza 2005;Munyaneza and Upton 2005;Munyaneza et al 2006Munyaneza et al , 2007aMunyaneza et al , 2008b. This is in contrast to potato purple top disease in the north central United States (Banttari et al 1993) and Mexico (Leyva-Lopez et al 2002) which is associated with the aster yellows phytoplasma and whose major vector is the aster leafhopper (Macrosteles spp.…”
Section: Introductionmentioning
confidence: 99%